Artificial Intelligence-Based Smart Power Systems - Sanjeevikumar, Padmanaban, 1978- (Hoboken, New Jersey : IEEE Press, Wiley, 2023)
"In the modern world, power distribution systems, microgrids, and electric vehicles have become absolute necessities due to various reasons. Smart power systems require more sophistication in operation and control. To achieve that sophistication, most of the loads in smart power systems are power electronics-based. However, this produces power quality problems like harmonics, flicker, etc. Power quality conditioners are essential to enhance the power quality in smart power systems. Hardware-in-the-loop (HIL)-based simulation is used to model smart power systems"--
Includes bibliographical references and index.
Keywords: Smart power grids; Artificial intelligence